Study of the Effect of pH on the Optical Properties of the CdTe Quantum Dots - Noori, Husham. N.; Abdulameer, Ameer F. (Iraqi Journal of Science, 2023)
This research aims to study the effect of different pH values on the growth of CdTe nanoparticles during specific times. The reflux method has been used as a method for preparing CdTe quantum dots. A difference in absorbance and intensities of peaks at pH 10.5 and 11.5 was observed during the reaction period. The growth rate of the NPs (nucleation) was irregular at low pH values. Optical examinations showed that the best growth rate of NPs was at pH value 12.